Pelacakan Kerusakan Akrosom Spermatozoa Domba Selama Proses Pembekuan dengan Teknik Histokimia Lektin (DETECTION OF ACROSOMAL DAMAGE OF RAM SPERMATOZOA DURING FREEZING PROCESS USING LECTIN HISTHOCHEMICAL TECHNIQUE) - Fannessia, Lisa Dwi; Karja, Ni Wayan Kurniani; Adnyane, I Ketut Mudite; Setiadi, Mohamad Agus (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Freezing process in ram spermatozoa caused damage of the plasma membrane and acrosome thatlead to the decrease of spermatozoa fertility. Research was conducted to evaluate acrosomal damageduring freezing process using lectin histochemical technique. Semen was collected twice a week usingartificial vagina from 1-2 years old Garut ram. Immediately after collection, characteristic of semenquality was evaluated then diluted with Niwa and Sasaki Freezing (NSF) medium. Semen was loadedinto 0.25 mL mini straws and equilibrated at 4oC for two hours. Straws were then frozen and stored inliquid nitrogen. Evaluation of sperm characteristic (motility, viability and plasma membrane integrity)and acrosomal integrity were done during the freezing process. Detection of acrosomal integrity was observedusing Fluorescens isothiocyanate (FITC) and Avidin-Biotin-Complex (ABC) staining methods. Data ofcharacteristic spermatozoa and acrosomal integrity were analyzed using ANOVA. Result of the experimentsshowed that the percentage of motility, viability and plasma membrane integrity of spermatozoa before freezing (83 ± 2.7%; 88.8 ± 2.6%; 88.2 ± 3.7%) were significantly decreased (P<0.05) after equilibration (71± 4.2%; 84.2 ± 5.0%; 76.2 ± 1.3%) and after thawing (40 ± 3.5%; 61.08 ± 3.3%; 51.2 ± 10.4%). The percentageof intact acrosomal spermatozoa using FITC and ABC methods during freezing process were 93.63 ±2.73%; 88.04 ± 3.2% and 81.73 ± 4.77% VS 94.54 ± 0.26%; 88.17 ± 0.38% and 79.38 ± 2.06%, respectively.In conclusion, the characteristic of spermatozoa were significantly decrease (P<0.05) during freezing process.Furthermore, the integrity of acrosome spermatozoa can be well analyzed during freezing process by usinglectin histochemical staining methods.
Keywords: acrosome, spermatozoa, freezing, lectin